PENGARUH AUDIT INTERNAL TERHADAP PENEKANAN RISIKO KECURANGAN PADA PT POS FINANSIAL INDONESIA - Rohyana, Cahyat; Rahmadina, Moch Taufiq Fajar; Marismiati, Marismiati (LAND JOURNAL, 2024)
In a company, internal control or internal audit is essential to achieve the company's objectives by preventing actions that could harm the company itself. This research is conducted to understand the influence of internal audit on the suppression of fraud risk. The research is a quantitative study with primary data obtained through interviews, questionnaires, and literature studies. Internal audit (X) and Fraud Risk Suppression (Y) are the variables examined. The sampling technique used in this research is purposive sampling, with a total of 35 samples obtained. The data was collected through questionnaires distributed to all respondents, who are employees of PT Pos Finansial Indonesia. Subsequently, the data was processed using SPSS, involving Validity Test, Reliability Test, Normality Test, Spearman Rank Correlation Analysis, Simple Linear Regression Analysis, t-test and Coefficient of Determination Test. The Research results indicate that internal audit significantly influences the emphasis on fraud risk at PT Pos Financial Indonesia